Tantangan dan Strategi Integrasi Nilai-Nilai Kristiani dalam Implementasi Kurikulum Merdeka pada Jenjang SMP - Febrianus Selvin Sudiman; Cristian Seldjatem (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This study examines the integration of Christian values into the Merdeka Curriculum for Christian Religious Education (PAK) in junior high schools (SMP), focusing on the challenges and strategies for its implementation. The Merdeka Curriculum, introduced in 2022, offers flexibility in instructional design; however, its implementation in the field of PAK requires specific adaptations to maintain the relevance of Christian values such as love, justice, and responsibility. This study employs a descriptive qualitative approach using library research combined with empirical content analysis of various case studies in Indonesian Christian schools. The findings indicate that the primary challenges include resource constraints, the readiness of PAK teachers, technological infrastructure gaps, and the influence of secular digital culture. Effective strategies include the development of a contextual curriculum based on Christian values, the utilization of digital technology in learning, the enhancement of teachers’ professional competencies, and collaboration between schools, families, and churches. The implications of this study suggest that the integration of Christian values into the Merdeka Curriculum can foster the holistic character of junior high school students, equipping them with integrity, resilience, and the ability to face the challenges of the digital age.